KAJIAN KUALITAS BATU BATA MERAH MELALUI PEMANFAATAN BAHAN SEDIMENTASI BENDUNG KRUENG ACEH - Azmeri Azmeri; Devi Sundary; Diana Sapha (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2017)
Abstract : The condition of a high sedimentation at the Krueng Aceh dam can be a business opportunity for making the red bricks. This sedimentation condition occurs throughout the year and along the Krueng Aceh river that also can cause flooding and damage to infrastructure. Based on these problems, the study aims to assess the utilization of the sediment as basic material for red bricks production. This research method create and physical testing samples of bricks. Testing is done by using a sample piece of brick from the mixture of sediment material and material for normal bricks. The two types of bricks that have the absorptive capacity less than 20% and the level of dryness well marked with a shrill sound. Hardness is good for both types of bricks, it is marked with the scratches that are not too deep. Both types of bricks odor also have no salt content, which is marked with no white patches on a dry surface. Brick compressive strength of normal bricks (BMnor) is 381.05 kg/cm2, and brick with a mixture of sediment of Krueng Aceh dam is 215.34 kg/cm2. Both the results of the compressive strength are above the minimum standard required by SNI 15-2094-2000 ie 50 kg/cm2. Through this study, it is expected that sedimentary material can be used as material for the manufacture of red bricks and boost the economy of the industry of red bricks around Banda Aceh and Aceh Besar.Keywords : red brick, sedimentary material, Krueng Aceh, compressive strength.Abstrak: Kondisi sedimentasi yang tinggi pada Bendung Krueng Aceh dapat menjadi peluang perkembangan usaha pembuatan batu bata merah. Kondisi initerjadi sepanjang tahun dan di sepanjang ruas sungai Krueng Aceh yang dapat menyebabkan banjir dan kerusakan infrastruktur. Berdasarkan permasalahan tersebut, maka penelitian ini bertujuan untuk mengkaji penggunaan sedimen sebagai bahan pembentuk batu bata merah. Metode penelitian ini dengan membuat dan menguji fisik sampel batu bata. Pengujian dilakukan dengan menggunakan benda uji batu bata dari sampel campuran material sedimen dan batu bata produksi saat ini (bata normal). Kedua jenis batu bata tersebut memiliki daya serap kurang dari 20% dan tingkat kekeringan baik yang ditandai dengan bunyi nyaring. Kekerasannya baik untuk kedua jenis batu bata, ditandai dengan bekas goresan yang tidak terlalu dalam. Kedua jenis bau bata juga tidak memiliki kandungan garam, yang ditandai tanpa bercak-bercak putih di permukaan yang kering. Kuat tekan batu bata normal (BMnor)sebesar 381,05 kg/cm2 dan batu bata dengan campuran sedimen Bendung Krueng Aceh sebesar 215,34 kg/cm2. Kedua kuat tekan di atas standar minimal SNI 15-2094-2000 yaitu 50 kg/cm2. Melalui kajian ini, diharapkan bahan sedimen dapat dimanfaatkan untuk pembuatan batu bata merah dapat meningkatkan perekonomian kelompok industri batu bata merah di sekitar Banda Aceh dan Aceh Besar.Kata kunci : Batu bata merah, bahan sedimen, Krueng Aceh, kuat tekan.